Temporal correlations imaging fixed targets through turbulence - Gulich, Maximiliano Damián (2016)
We study the temporal correlations from dynamic imaging through turbulence using incoherent light from fixed highcontrast targets. We conduct our experiment in controlled laboratory conditions using several values of the C2 n constant from the weak to strong fluctuation regime. We employ detrended fluctuation analysis to measure long-range correlations while considering scintillation information for every recorded pixel. We find that turbulence strength generally increases temporal correlations in time series from pixels in high-contrast regions of the image.